Variation of blood pressure among the adolescent students - Mushroor, Sumaiya; Islam, Md Ziaul; Amir, Riyadh Ahmed; Ahmed, Nafiza; Amin, Md Rasul (Bangladesh Medical Journal, 2016)
The increase in the burden of chronic disease associated with dietary and life style changes is of growing concern in Bangladesh and the adolescents are at the forefront of these changes. A very few studies have been carried out on the dietary intake, nutritional status and lifestyle pattern of adolescent in Bangladesh. This cross sectional study was carried out to determine the variation of blood pressure among adolescents and its association with socio-demographic factors, personal habits, dietary habits and body mass index. The study was conducted among one hundred and thirty students of adolescent age from selected school and college in Dhaka city during January to June 2012. Among 130 adolescents majority (50.8%) were male and 49.2% were female but no association was found between blood pressure and sex of the adolescent. Among the adolescents, 69.2% perform physical exercise but no association was found between the blood pressure and the exercise habit of the adolescent students. Among all the adolescents, 12.3% were smoker. The study assessed the association between blood pressure and smoking habit of the adolescent students & it was significant. Majority (70.80%) of the adolescents had history of taking extra salt but no association was found between the blood pressure and extra salt intake habit. Majority of the adolescent (86.2%) used to take fast food regularly but no association was found between the blood pressure and fast food intake habit. Majority of the adolescent 58.5% had positive family history of hypertension but no association was found between the blood pressure and family history of hypertensio. Among the adolescents, 40.0% had mental stress but no association was found between the blood pressure and mental stress. The study assessed the association between blood pressure and BMI of the adolescent students. But no association was found between the blood pressure and BMI. These findings might not have revealed the true picture regarding variation of blood pressure among adolescents and identify the risk factors responsible for this variation because the time was limited and sample size was small. Bangladesh Med J. 2015 Jan; 44 (1): 21-25